Effect of the inclusion of rumen-protected amino acids in the diet of growing beef cattle on animal performance and meat quality - Cabezas, Almudena; De la Fuente, Jesús; Díaz, María Teresa; Bermejo-Poza, Rubén; del Olmo, Diego Martínez; Mateos, Javier; Llanes, Nuria; Jimeno, Vicente (Frontiers in Animal Science, 2023)
This study investigated the impact of rumen-protected amino acids on beef cattle's growth, fattening performance, and meat quality. Two groups of 40 Montbeliard steers (237.8 ± 30 kg body weight) were housed separately and fed, with mono-tunnel feeders, either a control diet (CON) or a diet containing rumen-protected lysine and methionine with 3% less crude protein (APR). Feed consumption and weight were tracked in all animals, and meat quality analysis focused on the longissimus muscle, with 10 steers randomly selected from each treatment. Results for overall performance revealed no significant differences in body weight, average daily gain (ADG), and concentrate conversion ratio between the CON and APR diets (p > 0.05). However, during the final 90 days of the trial, the APR group showed significantly higher ADG (p < 0.05) than the CON group, while the concentrate conversion ratio was significantly higher (p < 0.05) in the CON group compared to the APR group. The hot carcass weight, dressing percentage, and carcass conformation did not differ significantly between the CON and APR diets (p > 0.05). There was a slight tendency (p = 0.06) for higher fatness score in the CON group. Regarding meat composition, the diet did not significantly affect proximate composition, but a tendency (p = 0.059) for higher crude protein content in APR cattle's meat compared to the CON group was observed. The APR meat showed slightly lower levels of C17:1 (0.56% vs. 0.72%) and C18:1n9 (31.7% vs. 34%), There was a tendency for C14:0 to be lower (P = 0.07), and for C16:0, C18:2 and polyunsaturated fatty acids (PUFA) to be greater in meat from cattle fed APR compared to CON. However, meat quality attributes like pH, water-holding capacity, color, and texture were similar in both CON and APR groups (p > 0.05). The findings indicate that utilizing rumen-protected amino acids enables formulating diets with reduced crude protein levels while enhancing nitrogen utilization efficiency for protein synthesis in intensively reared steers. Importantly, these dietary improvements do not adversely affect meat quality